Impact of Aerobika® oscillating positive expiratory pressure in improving small airway resistance, lung function, symptoms and exercise capacity in chronic obstructive pulmonary disease - Sahardin, Siti Nurhanis; Jailaini, Mas Fazlin Mohamad; Abeed, Nik Nuratiqah Nik; Ban, Andrea Yu-Lin; Hau, Ng Boon; Azmel, Azat Azrai; Shah, Shamsul Azhar; Hamid, Mohamed Faisal Abdul (Frontiers in Medicine, 2023)
Background Aerobika® oscillating positive expiratory pressure (OPEP) device promotes airway clearance in many respiratory diseases. However, studies have yet to focus on its effectiveness in improving small airway resistance via impulse oscillometry (IOS) measurement in COPD subjects. We aim to evaluate the improvement of small airway resistance (via IOS), lung function (spirometry), exercise capacity [via 6-min walking test (6MWT)], symptoms [COPD assessment test (CAT)] and severe exacerbation events among COPD subjects using Aerobika® OPEP. Methods This was a prospective, single-arm interventional study among COPD subjects with small airway disease. Subjects were instructed to use twice daily Aerobika® OPEP (10 min each session); for 24 weeks; as an additional to standard therapy. IOS, spirometry, 6MWT, CAT score and severe exacerbation events were evaluated at baseline, 12 weeks and 24 weeks. Results Fifty-three subjects completed the study. Aerobika® usage showed improvement of IOS parameters; e.g. measurement of airway resistance at 5 Hz (R5), cmH20/L/s, (12-week p = 0.008, 24-week p < 0.001), R5% predicted (12-week p = 0.007, 24-week p < 0.001) and small airway resistance (R5–R20), cmH20/L/s, (12-week p = 0.021, 24-week p < 0.001). There were improvement of lung function; e.g. FEV1, L (12-week p = 0.018, 24-week p = 0.001), FEV1% predicted (12-week p = 0.025, 24-week p = 0.001), FEF25–75, L (12-week p = 0.023, 24-week p = 0.002), and FEF25–75% predicted (12-week p = 0.024, 24-week p < 0.001). CAT score improved at 12 weeks (p < 0.001) and 24 weeks (p < 0.001). Subjects had improved exercise capacity (6MWT, metres) after 24 weeks (p = 0.016). However, there was no significant difference in severe exacerbation events 24 weeks before and after Aerobika® usage. Conclusion Aerobika® OPEP demonstrated significant improvement in small airway resistance as early as 12 weeks of usage, with sustained improvement at 24 weeks. Aerobika® OPEP administration had significantly improved lung function, 6MWT, and CAT scores over 24 weeks. There was no difference in severe exacerbation events.